Harmonizing Foam and Function: Clubhouse Design in Apartment Complexes - Ms. Ayesha Rafi; Deepti Pande Rana; Madhavendra Pratap Singh (International Journal of Architectural Design and Planning, 2024)
The increasing demand for urban living has led to the proliferation of apartment complexes, where common spaces like clubhouses play a pivotal role in fostering community and enhancing residents' quality of life. However, many existing clubhouses fail to harmonize form (aesthetic design) and function (practical usability), resulting in spaces that are visually appealing but underutilized or, conversely, highly functional but lacking in ambiance. This research addresses the critical issue of creating clubhouses that effectively integrate both form and function, ensuring that they serve the diverse needs of residents while also contributing to the overall aesthetic of the apartment complex.. The research findings provide a framework for architects, designers, and developers to create versatile, adaptable, and inclusive clubhouse spaces that promote social interaction, cater to a wide range of activities, and enhance the overall living experience. The study ultimately aims to inform future designs, ensuring that clubhouses in apartment complexes are both beautiful and practical, meeting the evolving needs of urban communities.
Keywords: aesthetic; harmonize; social interaction; visually appealing